Performance-related specifications for PCC pavements in Kansas - Gedafa, Daba S.; Hossain, Mustaque; Ingram, Lon S.; Kreider, Rick (My University, 2012)
Statistical specifications for highway construction provide the means to measure the important quality control attributes and ensure their compliance. The pay adjustments in these specifications reflect the amount of pay reduction and the optimized risk distributed between the owner agency and the contractor. The Kansas Department of Transportation (KDOT) has built a comprehensive database of as-constructed properties of materials for Portland Cement Concrete (PCC) pavements from the tests required as part of the Quality Control/Quality Assurance (QC/QA) program. Currently, KDOT pays incentives/disincentives for thickness and strength for PCC pavements. A practical performance model and composite index that include these two quality characteristics (thickness and strength) and air content (for durability) are needed to reflect the combined effect on the performance of PCC pavements. The main objectives of this study were to investigate the effect of levels of significance and lot size, and to develop practical performance model and composite index for PCC pavements in Kansas. Thirteen projects from four administrative districts of KDOT were selected for this study. Statistical Analysis Software (SAS) was used for statistical analysis. Microsoft excel was used to develop the performance models. Lot-wise comparison showed that QC means are significantly different in most of the cases. These cases increase with an increase in significance level. A practical performance model and composite index using quality characteristics (thickness, strength, and air content) have been proposed as an integral part of performance-related specifications (PRS) in Kansas.
Keywords: Performance-related specifications (PRS); Composite index; Portland cement concrete (PCC) pavements; Pavements; Kansas